An Organic Zeolite With 10 Å Diameter Pores Assembles From a Soluble and Flexible Building Block by Non‐Covalent Interactions. Issue 4 (8th April 2019) - Plater, M. John; Harrison, William T. A.
Abstract: Two similar molecular building blocks, which both contain a hydrogen‐bonded nitro group, have been prepared and crystallised. One structure has more flexibility with a butyl side chain which allows an open framework organic zeolite to form with large 10 Å diameter pores, whereas the other structure has less flexibility with an aryl side chain and is close packed. The pore size is comparable with those of the aluminophosphate VPI‐5 (12 Å). It is concluded that some flexibility in the design of the building block for porous organic molecular materials was beneficial. Abstract : Keep it flexible ! Hydrogen bonding directs the cylindrical assembly of a hexamer motif which packs forming an organic zeolite with large 10 Å pores. Molecular design and synthesis serve to exemplify some principles required to form porous organic solids.